Pemenuhan Kewajiban Dan Tanggung Jawab Pemerintah Daerah Terhadap Hak Pendidikan Anak Di Kabupaten Bangka Selatan - Dewi, Virna; Rindiani, Anis; Yuliana, Sri; Pawari, Rahmianti Ranti (VIVA THEMIS, 2024)
One of the principles of a rule of law is the principle of legality, which means that every government legal action must be based on applicable laws and regulations or every government legal action must be based on the authority granted by laws and regulations. By relying on the principle of legality, the government carries out various legal actions. Because every legal action implies the use of authority, it implies an obligation to be responsible. In accordance with the principle "geen bevoegodheidzonder verantwoordelijkheid." The government's responsibility towards citizens or third parties is adhered to by almost all countries based on law. It is clear that every use of authority contains responsibility, however, it must also be stated about the methods of obtaining and exercising authority. Because not all state administration officials who carry out government authority automatically bear legal responsibility. Each country has its own laws and regulations. There is a juridical basis for education in Indonesia which has a set of laws and regulations which are the starting point for the education system in Indonesia. In the future, we will find that there are still many laws that have not achieved their goals, because the Indonesian nation is a pluralistic nation, therefore it is certainly not easy to achieve all goals quickly and briefly. To achieve our educational goals we need positive support from all aspects of society, education providers and the government. because the aim of providing good education and in accordance with educational foundations and implementing education based on law is to make education providers focused, orderly and in accordance with the roots of national culture. The formulation of the problem in this writing is how to analyze the implementation of the right to education as a constitutional right in Indonesia. The type of research that will be used in writing this law is normative and empirical research. This is basically a combination of a normative legal approach with the addition of various empirical elements.